Improvement Mathematics Learning Outcomes Through Demonstration Method in Fourth Grade Students of SDN KESEK 1 - Annisa Hariyati; Hesty Widyaning Tyastuti; Dwi Safitri; Agung Setyawan; Javier Tubío Ordóñez (Journal of Action Research in Education, 2025)
The aim of this research is to determine the process of using the demonstration method in mathematics learning on the area of square and rectangular shapes and improving student learning outcomes on the area of flat shapes through the demonstration method.The type of research used is classroom action research (PTK) which has 2 cycles. Each cycle consists of planning, implementation, observation and reflection. The data collection techniques used were interviews, tests, observation and documentation. The research instrument is a test sheet on student learning outcomes. The subjects of the research were all class IV students for the 2023/2024 academic year, totaling 25 students consisting of 12 male students and 13 female students.The results of the research show that the application of the demonstration method can improve student learning outcomes which achieve a score above 70 with a percentage of complete learning outcomes, pre-cycle 28% with an average score of 56.8, Cycle I 60% with an average score of 68 and Cycle 2 96% with average 81.2. Based on the research, it can be concluded that learning mathematics about the area of square and rectangular shapes by applying the demonstration method can be successful, so it can be used as an alternative solution to improve mathematics learning at UPTD SDN Kesek 1.